Drug Testing/Use - Klein, Sandra S. (1994)
Drug testing is one of the most controversial of recent privacy issues. The bibliography which follows provides the reader with access to a wide range of discussion on this topic which is, or should be, of interest to everyone. Whether in our private lives, or on the job, drug use and drug testing will have an impact on every one of us